From physics to daily life : applications in biology, medicine, and healthcare - Bressan, Beatrice (Weinheim an der Bergstrasse, Germany : Wiley Blackwell, 2014)
Beatrice Bressan brings together a number of outstanding examples of successful cross-disciplinary technology transfer originating in fundamental physics research, which dramatically impacted progress in biomedical research and clinical applications. Many of these examples were developed at CERN, a hotbed of fundamental inventions in particle physics. Additional sections of the book deal with knowledge management and technology transfer including its economic aspects. While each chapter has been drafted by an expert in the field, the editor has carefully edited the whole book, ensuring a coh.
6.2.1.1 Single Gene Expression Analysis: Real-Time PCR6.2.1.2 Microarrays-Based Transcriptomics; 6.2.1.3 Deep Sequencing; 6.2.2 Classical Biochemistry Goes -Omics; 6.2.2.1 Proteomics; 6.2.2.2 Metabolites; 6.2.2.3 Metabolomics; 6.3 Omics Output (I): Knowledge Bases; 6.3.1 Human Genome Projects; 6.3.2 Human Proteome Projects; 6.3.3 Human Metabolome Projects; 6.4 Omics Output (II): Translations and Challenges; 6.4.1 Genetics to Diagnostics; 6.4.2 Proteomics to Diagnostics; 6.5 From Omics to 'Know-mics': Translation into Personal and Actionable (gen)omics; 7 Technology Fallout in Bioinformatics.
Include indexes.
Description based on online resource; title from PDF title page (ebrary, viewed August 30, 2014).
Keywords: 2000-2099; Science -- History -- 21st century; Science -- Social aspects -- Forecasting; Science; Science -- Social aspects -- Forecasting; Science -- History -- 21st century; Science -- Social aspects -- Forecasting; Science; SOCIAL SCIENCE -- General; Electronic books; History; Electronic books